E-BOSS: an Extensive stellar BOw Shock Survey : I. Methods and first catalogue - Peri, Cintia Soledad (2012)
Context. Bow shocks are produced by many astrophysical objects where shock waves are present. Stellar bow shocks, generated by runaway stars, have been previously detected in small numbers and well-studied. Along with progress in model development and improvements in observing instruments, our knowledge of the emission produced by these objects and its origin can now be more clearly understood. Aims. We produce a stellar bow-shock catalogue by applying uniform search criteria and a systematic search process. This catalogue is a starting point for statistical studies, to help us address fundamental questions such as, for instance, the conditions under wich a stellar bow shock is detectable. Methods. By using the newest infrared data releases, we carried out a search for bow shocks produced by early-type runaway stars. We first explored whether a set of known IRAS bow shock candidates are visible in the most recently available IR data, which has much higher resolution and sensitivity. We then carried out a selection of runaway stars from the latest, large runaway catalogue available. In this first release, we focused on OB stars and searched for bow-shaped features in the vicinity of these stars. Results. We provide a bow-shock candidate survey that gathers a total of 28 members, which we call the Extensive stellar BOw Shock Survey (E-BOSS). We derive the main bow-shock parameters, and present some preliminary statistical results on the detected objects. Conclusions. Our analysis of the initial sample and the newly detected objects yields a bow-shock detectability around OB stars of ∼10 per cent. The detections do not seem to depend particularly on either stellar mass, age or position. The extension of the E-BOSS sample, with upcoming IR data, and by considering, for example, other spectral types as well, will allow us to perform a more detailed study of the findings.